2014
DOI: 10.1038/srep05634
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate herbicide affects belowground interactions between earthworms and symbiotic mycorrhizal fungi in a model ecosystem

Abstract: Herbicides containing glyphosate are widely used in agriculture and private gardens, however, surprisingly little is known on potential side effects on non-target soil organisms. In a greenhouse experiment with white clover we investigated, to what extent a globally-used glyphosate herbicide affects interactions between essential soil organisms such as earthworms and arbuscular mycorrhizal fungi (AMF). We found that herbicides significantly decreased root mycorrhization, soil AMF spore biomass, vesicles and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(102 citation statements)
references
References 79 publications
4
94
2
2
Order By: Relevance
“…Negative effects of glyphosate, supportive of the findings in the present study, have been recently reported by Druille et al (2013) and Zaller et al (2014). Causes of negative effects may be direct, i.e., damage to the external hyphae and/or AM spores, or indirect, as where root exudate production is reduced by the herbicideinduced death of targeted host plants, as in T1 and T2 at Elgin, where the tree rows were kept mainly weed-free with glyphosate.…”
Section: Effects Of Year Season and Treatment On Am Parameterssupporting
confidence: 90%
“…Negative effects of glyphosate, supportive of the findings in the present study, have been recently reported by Druille et al (2013) and Zaller et al (2014). Causes of negative effects may be direct, i.e., damage to the external hyphae and/or AM spores, or indirect, as where root exudate production is reduced by the herbicideinduced death of targeted host plants, as in T1 and T2 at Elgin, where the tree rows were kept mainly weed-free with glyphosate.…”
Section: Effects Of Year Season and Treatment On Am Parameterssupporting
confidence: 90%
“…It should be noted, however, that water infiltration is highly heterogeneous in space (Hassler et al 2014), and that the experiment was performed in intact soil, rather than in a homogenised substrate. Water infiltration may indeed be unpredictable even under highly controlled conditions: for instance, in a greenhouse experiment that simulated a heavy rainfall event similar to ours (40 mm), anecic earthworms increased water infiltration (Zaller et al 2011), but the effect was not repeatable in a subsequent experiment with similar methodology (Zaller et al 2014).…”
Section: Discussionmentioning
confidence: 70%
“…With the increased use of glyphosate-based herbicides, the occurrence of glyphosate and its metabolite AMPA derived from intensive agriculture triggers great attention being paid on the risks of glyphosate in environment (Qiu et al, 2013;Zaller et al, 2014). In highly erodible land, together with runoff and suspended load, glyphosate and AMPA, supposedly, are transported, deposited, and probably accumulated in nearby areas (Ulén et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The repetitive use of glyphosate-based herbicides in the field, however, increases the possibility of glyphosate occurrence in, and threat to, soil, plants, surface/ground water (Borggaard and Gimsing, 2008), and animals (Lanctot et al, 2013;Muangphra et al, 2014;Yadav et al, 2013;Zaller et al, 2014). Meanwhile, the risk is particularly high when applied pesticide on bare soil directly before and after sowing.…”
Section: Introductionmentioning
confidence: 99%